DEVELOPMENT OF COMPOSITION AND TECHNOLOGY FOR PRODUCTION OF NONALCOHOLIC BEVERAGE CONCENTRATE TABLET - Shkolnikova M.N.; Averyanova E.V.; Donya D.V.; Khlopotov I.V. (Техника и технология пищевых производств, 2017)
The high and stable demand for dry concentrates of nonalcoholic beverages prepared on the basis of extracts of fruit raw materials is primarily due to the simplicity and convenience of storage, transportation and use. As a result of monitoring of trade proposals, it has been found that unlike tablets, powdered and granulated concentrates are the most widely distributed in this segment of the food market. The formulation and technology of the concentrate of non-alcoholic thirst-quenching beverage in the form of tablets has been developed, the distinguishing feature of which is the use, as a flavor component, of the dry extract of cowberry berries obtained by vacuum-pulse extraction. The influence of the ratio of components in the concentrate on organoleptic characteristics of the product has studied and their optimum ratio has been determined, g/10 g of the composition: fruit-berry extract - 3.5, fructose - 4.4, citric acid - 1.0, sodium carbonate - 0.5, magnesium carbonate - 0.2, calcium carbonate - 0.4. It is shown that the introduction of 3% of starch from the weight of the composition helps reduce adhesion properties, reduce dissolution time, increase strength and improve the appearance of the tablets, while maintaining a constant taste level of the product. To obtain aconcentrate of non-alcoholic beverage in the form of tablets with given dimensional-mass characteristics: diameter 20 mm, height 5 mm, weight 2 g the optimum parameters of the tablet preparing process have been established: pressing force 10 MPa; Holding the tablet under load for 30 seconds. The best method of obtaining feedstock compositions is mixing the original components of the composition in a mixer of loose components, followed by granulation, while the dissolution time of the concentrate in 200 cm3 of room temperature water is 70 seconds.